Serum Expression Level of MicroRNA-122 and its Significance in different Stages of Hepatitis B Virus Infection: MicroRNA-122 and its effects on Hepatitis B - Singh, Shashi Prabha; Maurya, Vandana; Kumar, Krishan; Singh, Durgesh; Verma, Poonam; Samanta, Dipan; Verma, Manish Kumar (Cellular and Molecular Biology, 2023)
This study aims to determine the serum expression level of miRNA-122 and its significance in the different stages of Hepatitis B virus infection. The study subjects were recruited and grouped for Hepatitis B associated with Chronic Hepatitis B infection, hepatic sclerosis, hepatocellular carcinoma, and healthy controls were also considered. Venous blood was collected from the participants including the controls and routine blood tests and quantification of miRNA-122 were done and analyzed in each case of hepatitis B infection and compared with that of healthy controls. The miRNA-122 was determined, which came to be highest in patients with Chronic Hepatitis B while patients with hepatic sclerosis and patients with hepatocellular carcinoma showed a subsequent number of copies. The number of copies of miRNA-122 in the CHB, hepatic sclerosis, and HCC group was significantly higher than in the healthy control. The quantification of miRNA-122 and subsequently plotting the ROC curve has shown that miRNA-122 can be considered as a biomarker of hepatitis B for screening and diagnosis purposes.